STRATEGI BERTAHAN UMKM PADA MASA PANDEMI COVID-19 PADA PEMBIAYAAN BANK THITIL UNTUK PARA PEDAGANG - fatimah evanggalista wijayanti; Badriyah, Nurul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
One of the sectors most affected by the policies issued by the goverment due to the Covid-19 pandemic is the MSME sector. whereas in fact, MSMEs are the main actors in economic activities in Indonesia. MSMEs are also the largest provider of employement. The decline in people's purchasing power has an effect on the decline in the income of the MSME sector so that the MSME sector is required to have a strategy on how their business can survive or they can still obtain capital to produce further. This study uses field research or field research where researchs conduct research and collect data directly and see the actual phenomenon. The results showed that the traders' survival strategy was to do financing in the informal sector of Bank Thitil because it was considered an easy process and fast time. Compared to other formal or informal sectors. Bank Thitil is the easiest solution because there is no need for collateral as loan collateral. The diffulty experienced by traders is that the interest rates given are too high, so to cover loans in one sector the traders make loans to other sectors so as to multiply the loans they have and bear very high interest rates.